An evaluation of alternative biodegradable and reusable drinking straws as alternatives to single‐use plastic. Issue 7 (12th June 2021) - Jonsson, Amanda; Andersson, Kent; Stelick, Alina; Dando, Robin
Abstract : Abstract: The manufacture of single‐use plastic items uses fossil fuels, and releases greenhouse gases. Plastic waste is also harmful to humans and wildlife. Recent attention towards the regulation or elimination of plastic straws has led to the development of many alternatives to single‐use plastic straws, some intended to be disposed of immediately after use, and others to be cleaned and reused. Unfortunately, anecdotes are widespread of inferior sensory experiences from such alternatives, with straws either losing stability when wet, imparting negative flavor properties to a beverage, or feeling unpleasant in the mouth. Despite such reports, little formal research exists categorizing these alternatives. Here, we examine popular choices for straw materials in a focus group ( n = 9) and in a consumer sensory test ( n = 102), as well as testing the durability of straws when soaked in water. Cornstarch straws offered the most similar sensory experience to plastic, whereas options such as paper, wheat, pasta, and rice straws all scored low on mouthfeel and flavor liking, with off‐flavors commonly reported in beverages consumed with these straws. A Kano analysis ( n = 193) to determine the factors consumers find essential in drinking straws confirmed the most important to be that no flavors were imparted to beverages when used. Finally, a consumer survey ( n = 579) confirmed that straw consumers primarily use them out of default availability; most use them only if they are given without asking, and most would readily give up plastic straws, but may be unfamiliar with other options. Practical Application: Plastic straws contribute to waste and result in the release of greenhouse gases in their manufacture. Despite this, they provide a superior sensory experience compared to other options. Here, we review aspects of this experience, along with consumers motivations for using straws.